Le panoptisme horizontal ou le panoptique inversé - Simon BOREL (Tic & Société)
Horizontal panopticism increasingly appears as the typical shape of power in a networked society. This article tries to understand how online reticular panopticism emerges at the intersection of digital social media, cognitive capitalism and digital giants, neoliberal governance and the contemporary democratic dynamic of recognition. It is characterized by the control and monitoring of all by all on networks through the quest for online visibility and celebrity, the renewal of state monitoring systems via the Internet, and the control of consumers by the business world. This article shows how horizontal panopticism is, to some degree, inversely symmetrical to the totalitarian panopticon model, a model that it is simultaneously very distant from yet at the same time and very close to.